A Comparative Proteomics Analysis of Five Body Fluids: Plasma, Urine, Cerebrospinal Fluid, Amniotic Fluid, and Saliva. Issue 6 (13th June 2018) - Zhao, Mindi; Yang, Yehong; Guo, Zhengguang; Shao, Chen; Sun, Haidan; Zhang, Yang; Sun, Ying; Liu, Yaoran; Song, Yijun; Zhang, Liwei; Li, Qian; Liu, Juntao; et al.
Abstract : Purpose: Body fluid is considered a rich source of disease biomarkers. Proteins in many body fluids have potential clinical applications for disease diagnostic and prognostic predictions. Experimental design: To determine differences in the protein components and functional features of body fluids, a proteomic comparison of five body fluids (plasma, urine, cerebrospinal fluid, saliva, and amniotic fluid) was conducted by high‐resolution mass spectrometry. Results: A total of 4717 nonredundant proteins were identified, and the concentrations of 3433 proteins were estimated by an intensity‐based algorithm quantitation method. Among them, 564 proteins were shared among the five body fluids, with common functions in the coagulation/prothrombin system and inflammatory response. A total of 36.7% of the proteins were detected in only one body fluid and were closely related to their adjacent tissues by function. The functional analysis of the remaining 2986 proteins showed that similar functions might be shared among different body fluids, which highlighted intimate connection in the body. Conclusions and clinical relevance: The quantitative comparative functional analysis indicated that body fluids might reflect the diverse functions of the whole body rather than the characteristics of their adjacent tissues. The above data might indicate the potential application of body fluids for biomarker discovery.